Poster Presentations - Team, Editorial (South African Journal of Enology and Viticulture, 2017)
THEME I - A Worldwide Perspective on Viticultural Zoning THEME II - Methodological Approach to Zoning THEME: III - Practical Application of Zoning THEME IV - Viticulture, Landscapes and the Marketing of our Wine THEME VI - Role of Climate/Soil of Different Zones/Terroirs on Grape Characteristics THEME VII - Role of Trellising System and Canopy Size/Exposure in Zone/Terroir Expr~ssion IBEME VID -The Role of Soil Water Holding Capacity and Plant Water Relations in Zone/Terroir Expression TI:IEl\ilE IX - Role ~f Harvesting Time/Optimal Ripeness (Evolution of. Ripening) in Zone/Terroir Expression THEME XII~ Tools for Optimizing Grape and Wine Quality